TAFSIR SURAT AL-ALAQ AYAT SATU SAMPAI LIMA: (Tela’ah Konsep Pendidikan Islam Perspektif M. Quraish Shihab) (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2020)
Al-Alaq verses explain human creation from a clot of blood. The research finding shows that the concept of Islamic education according to M. Quraish Shihab are (a) The purpose of Islamic education is the formation of a nurtured human who includes physical, mental, and intellect (b) reading the name of Allah SWT (bismi Rabbik) when doing all works (c) there is an interdependent nature of humans, since they are social creatures (d) reading it repeatedly, and sincerity will gain new knowledge, understanding, and insight. (e) Allah will give knowledge to everyone who has taught it with or without tools (kalam). Therefore, self-improvement is important to increase devotion to Allah.